Cost-effectiveness analysis of ceftazidime-avibactam as definitive treatment for treatment of carbapenem-resistant Klebsiella pneumoniae bloodstream infection - Kong, Wenqiang; Yang, Xueting; Shu, Yunfeng; Li, Shiqin; Song, Bihui; Yang, Kun (Frontiers in Public Health, 2023)
Background: Ceftazidime-avibactam (CAZ-AVI) is a novel antibiotic that has been confirmed in the United States and China for use in patients with carbapenem-resistant Klebsiella pneumoniae (CRKP) bloodstream infection (BSI). However, the cost-effectiveness of CAZ-AVI is unknown in China. This study aimed to evaluate the cost-effectiveness of CAZ-AVI compared to polymyxin B (PMB) monotherapy or PMB-based therapy for the treatment of CRKP BSI from the Chinese healthcare perspective. Methods: A hybrid decision tree and Markov model were constructed for a hypothetical cohort of patients with CRKP BSI. The time horizon of the Markov model was 5 years with an annual discount rate of 5% used in both costs and quality-adjusted life-years (QALYs). The model data was derived from published literature and publicly available database. Regimens with an incremental cost-effectiveness ratio (ICER) lower than the willingness-to-pay (WTP) threshold of 11,600 per QALY were considered cost-effective. Deterministic and probabilistic sensitivity analyses were performed to examine the robustness of model analysis. Results: In the base-analysis, CAZ-AVI provided an additional 0.06 QALYs and reduced the cost by 2,218.3, yielding an ICER of -36,730.9/QALY, well below the WTP threshold of 11,600 per QALY when compared with PMB-based therapy. CAZ-AVI provided an additional 0.35 QALYs and increased the cost of 208.4, producing an ICER of 591.7/QALY that was below the WTP threshold compared to PMB monotherapy. At a 11,600/QALY threshold, results were sensitive to the cost of PMB-based strategy, the cost of CAZ-AVI strategy, the probability of cure with CAZ-AVI, and the probability of cure with PMB or PMB-based therapy. CAZ-AVI was an optimal regimen in 76.9% and 80.8% of 10,000 Monte Carlo simulations at 11,600/QALY and 34,800/QALY, respectively. Meanwhile, CAZ-AVI was cost-effective at the WTP thresholds of all 31 Chinese provinces in 61.4% (Gansu) to 83.1% (Beijing) of simulations. Conclusions: Ceftazidime-avibactam is expected to be a cost-effective treatment compared with PMB monotherapy or PMB-based therapy for CRKP BSI from the Chinese healthcare perspective.